Liposomal Formulation of Monovalent Cholesteryl Cytofectins with Acyclic Head Groups and Gene Delivery: A Systematic Review - Ariatti, Mario (Current Pharmaceutical Biotechnology, 2015)
A large number of liposome-based non-viral gene and siRNA delivery systems include monovalent cholesteryl cytofectins with acyclic head groups in their formulations. Progress in their clinical development has, however, been hampered by relatively low transfection efficiencies. Structural differences between members of this class of cationic amphiphiles are located primarily in their linker, spacer and head group regions. This review examines the structural diversity encountered in each of these domains and seeks to identify those features linked to favourable transfection activity. Thus the ether linker, with its greater chemical and metabolic stability, is associated with higher transfection activity than ester, amide or carbamoyl tethers. While a medium length 6 atom spacer in the ether series is preferred over shorter spacers for enhanced activity, short (2 atom) to long (11 atom) spacers are effective in the more common carbamoyl series. For largely historic reasons, the dimethylamino head group has remained a popular cationic centre, but several studies have shown that the N-hydroxyethyl secondary amine functionality may be more effective in cytofectins. This observation has been attributed, in part, to the increased hydrophilicity of the head group and facilitated release of the nucleic acid cargo from liposomes in endosomal compartments. However, the hypothesis that the incorporation of each of these favourable chemical features into a single novel cytofectin may lead to superior transfection activity remains to be fully tested.
Keywords: Cholesterol